Modelling and motion analysis of five-bar 5R mechanism - Budniak, Zbigniew; Bil, Tadeusz (Zielona Góra: Uniwersytet Zielonogórski)
This article presents the use of the potential of the present-day CAD/CAE systems in modelling and a kinematic analysis of a spatial five-membered lever mechanism 5R. A simulation model was developed. On the grounds of the methodology developed, numerical analysis was conducted. The results of the analysis are presented in diagrams.
Keywords: CAD/CAE; numerical analysis; spatial dimension chain; collision; trajectory